Run Away - Coben, Harlan, 1962- (New York, NY : Grand Central Publishing, 2020)
Youve lost your daughter. Shes addicted to drugs and to an abusive boyfriend. And shes made it clear that she doesnt want to be found. Then, by chance, you see her playing guitar in Central Park. But shes not the girl you remember. This woman is living on the edge, frightened, and clearly in trouble. You dont stop to think. You approach her, beg her to come home. She runs. And you do the only thing a parent can do: you follow her into a dark and dangerous world you never knew existed. Before you know it, both your family and your life are on the line. And in order to protect your daughter from the evils of that world, you must face them head on.
Keywords: Daughters -- Fiction; Drug addicts -- Fiction; Runaway women -- Fiction; Murder -- Fiction; New York (N.Y.) -- Fiction; Thrillers (Fiction)